The impact of ICTs (Robotics, VR, AI, Games) on gifted students’ education - David, Anthi; Kiose, Vasiliki; Maikou, Antonia; Tzelepi, Efi; Stathopoulou, Agathi (Eximia, 2023)
The entry of ICT into the education of gifted students is an important step towards the rapid change of the way in which the pedagogical process is carried out. The efforts to introduce ICTs in the education of gifted students are important, but they encounter expected difficulties, without their solution the effort will never prosper. The work you will read is a literature review. More specifically, in this work there is talk about giftedness, educational methods with the use of ICT and the needs both for the training of the educational staff and the configuration of the school space.